Investigation of deformation patterns by DS-InSAR in a coal resource-exhausted region with spaceborne SAR imagery. Issue 5 (1st June 2021) - Du, Yuling; Yan, Shiyong; Yang, Huaining; Jiang, Jinxiong; Zhao, Feng
Graphical abstract: Highlights: DS-InSAR could accurately locate the region influenced by underground mining operation. DS along with PS are more valuable in deformation estimation of low coherence region. The deformation characteristics are complex because of different mining activities. Abstract: Along with the impact of energy structure adjustment as well as the coal resource exhaustion in the old mining region, the deformation over the abandoned mine region has severely restricted both the reuse of abandoned lands and the sustainable urban development. Therefore, it is essential to conduct the long-term surface deformation observation in the abandoned coal region. In order to overcome the incoherence factors influencing performance of the traditional InSAR time series technique, the new InSAR time series approach integrating the distributed scatter targets (DS) was presented and applied in observation and analysis of surface deformation characteristics in coal resource exhaustion region. With the help of DS identification and corresponding phase optimization, the number of measurement points (MPs) increase from 92, 539 to 781, 364 in Peibei coal region with Sentinel-1 TOPS imagery, which make up for the deficiency caused by the uneven distribution of few points. Compared to the traditional TS-InSAR method, DS-InSAR results could efficiently improve the deformation identification ability with high reliability in coal regions. The monitoring result reveals that the surface became steady gradually along with the underground mining activities stop, but there is still some instability over the closed goaf because of the unstability of coal pillar and the improving surface loads. Thus the long-term surface monitoring should be carried out in old coal region, and the DS-InSAR would provide an efficient and reliable technical support for surface stability investigation in coal resource exhausted region.